The diagnostic value of perivascular infiltrates in muscle biopsy specimens for the assessment of rheumatoid vasculitis. Issue 2 (1st February 1998) - Voskuyl, Alexandre E; van Duinen, Sjoerd G; Zwinderman, Aeilko H; Breedveld, Ferdinand C; Hazes, Johanna M W
Abstract : OBJECTIVE: To determine the diagnostic value of perivascular infiltrates (PVI) in randomly obtained muscle biopsy specimens for the assessment of rheumatoid vasculitis (RV). METHODS: The number and size of PVIs, defined as the presence of mononuclear or polymorphonuclear cells around ⩾ 50% of the circumference of a vessel wall, as well as the presence of fibrinoid necrosis were determined in frozen sections of muscle samples of RV patients with histologically confirmed vasculitis in fixed muscle tissue (n=12). The findings were compared with those observed in frozen sections of muscle biopsy specimens of rheumatoid arthritis (RA) patients not suspected of vasculitis (n=14) and patients with osteoarthritis (OA) (n=11). The presence of PVIs and of fibrinoid necrosis were sought in four frozen sections of the muscle biopsy specimen. RESULTS: PVIs were observed in 75% of the RV patients, which was significantly (p < 0.05) higher than the frequency found in RA (14%) or OA (18%) patients. PVIs with ⩾ three cell layers were found in 67% of the RV patients and in none of the RA and OA patients (p < 0.05). Fibrinoid necrosis was found in least one of four frozen section in 33% of the RV patients. There was a good intra-observer and inter-observer concordance on the presence of fibrinoid necrosis and of PVIs with ⩾ three cell layers. CONCLUSIONS: The assessment of PVIs with ⩾ three cell layers in a muscle biopsy specimen is a specific and reliable test in discriminating RV from RA without vasculitis. The demonstration in muscle of PVIs with ⩾ three cell layers is more sensitive than that of fibrinoid necrosis in the diagnosis of RV.